Investigation of optimal condition for Chlorella vulgaris microalgae growth - S. Daliry; A. Hallajsani; J. Mohammadi Roshandeh; H. Nouri; A. Golzary (Global Journal of Environmental Science and Management)
Due to its abundance and also flexibility of cultivation conditions, Chlorella vulgaris microalgae is one of the most ideal options available in order to production of microalgae based biodiesel. Since vulgaris cultivation for fuel production needs economic considerations to be taken, and in first place providing biomass and lipid production costs is important, wide researches have been conducted in this field, and this study aims to spot the best condition for cultivation of this valuable specie by reviewing the whole research conducted. So far, Researchers' efforts show that, the best condition for vulgaris cultivation is mixotrophic regime which is done in a bubble column photobioreactor. Glucose as carbonic source and nitrate as nitrogen source, have the most efficacy among nutrition conditions. It is known the best results obtain in amounts glucose and nitrate of 20 and o.5 g/L respectively. Alkaline medium (pH 9 to 10), non-continuous illumination, 5 to 7 Klux and a 200 mL/min aeration flow rate, indicated the best physical conditions. The most vulgaris biomass amount produced was 3.43 g/L, and the best lipid productivity was measured 66.25 mg/L/day.